Evaluation of T cell infiltration in matched biopsy and nephrectomy samples in renal cell carcinoma. Issue 37 (September 2018) - Zahoor, Haris; Pavicic, Paul G.; Przybycin, Christopher; Ko, Jennifer; Stephens, Lisa; Radivoyevitch, Tomas; Jia, Xuefei; Diaz-Montero, Claudia Marcela; Finke, James; Rayman, Patricia A.; Gilligan, Timothy D.; Grivas, Petros; et al.
Abstract : Abstract: T cell infiltration in tumors has been investigated as a biomarker of response to checkpoint inhibitors. Neo-adjuvant studies in renal cell carcinoma (RCC) may provide a unique opportunity to compare T cell infiltration in a pretreatment renal mass biopsy to a posttreatment nephrectomy specimen, and thus evaluate the effects of immune checkpoint inhibitors. However, there are no data regarding the association of T cell infiltration in matched biopsy and nephrectomy samples without intervening treatment. Understanding this association will inform investigation of this potential biomarker in future studies. Matched biopsy and nephrectomy samples (without intervening systemic therapy) were identified from patients with nonmetastatic RCC. Selected tissue sections from biopsy and nephrectomy samples were reviewed and marked for intratumoral lymphocytes by a pathologist. Immunohistochemistry (IHC) was utilized to stain for T cell markers (CD3, CD4, and CD8). Intratumoral staining was then quantified in the tissue sections as counts per total tumor area surveyed. Spearman correlation (r) was used to measure associations. Thirty matched pairs were investigated. The median interval between biopsy and nephrectomy was 2.8 (0.2–87.7) months. Clear cell was the most common histology (29/30; 97%). There was a statistically significant positive correlation between the frequency of CD3 + and CD8 + T cells between matched biopsy and nephrectomy samples (r = 0.39; P = .036 and r = 0.38; P = .041, respectively). The frequencies of CD8+ T cells in matched biopsy and nephrectomy samples in RCC in the absence of intervening treatment have been characterized and show a positive correlation between matched biopsy and nephrectomy samples.